1987
DOI: 10.1104/pp.85.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Fate of Ethephon ([2-Chloroethyl]phosphonic Acid) in Dormant Weed Seeds

Abstract: Although ethephon (12-chloroethyllphosphonic and that ethephon will contribute to the buffer intensity of the test solution (diprotic acid, pka1 = 2.24, pka2 = 6.97; 2). In addition, ethephon degrades at a rate proportional to the fully dissociated species (dianion concentration) and the rate is markedly temperature dependent (2). In germination studies, relatively concentrated solutions of ethephon (1 mM) are often required to produce the desired response. Because these solutions are acidic, the rate of dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…1,2 The conversion of ethephon to ethylene takes place at higher pHs. Thus, ethylene can be easily prepared by hydrolyzing ethephon in buffered conditions.…”
Section: Purity Of Ethylene Prepared From Ethephon Decomposition and mentioning
confidence: 99%
“…1,2 The conversion of ethephon to ethylene takes place at higher pHs. Thus, ethylene can be easily prepared by hydrolyzing ethephon in buffered conditions.…”
Section: Purity Of Ethylene Prepared From Ethephon Decomposition and mentioning
confidence: 99%
“…Plants need oxygen for respiration and energy release. CO 2 fixation is limited by environmental stresses, such as cold and high temperature, drought, and salt stress which reduce NADP + regeneration and thus induce accumulation of ROS including hydrogen peroxide (H 2 O 2 ), superoxide radical (O 2− ), and hydroxyl radicals (OH − ) in leaves [45] [46]. Previous cotton research showed that premature leaf senescence, reflected as aggregated membrane damage, lipid peroxidation, and decreased photosynthesis, is a result of imbalance of ROS metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Ethephon decomposition results in the release of chloride, ethylene, and phosphate, which means non-ethylene responses may exist. In weed seed germination studies only a small portion of 14 Clabeled ethephon was released as ethylene [45]. Others have also shown low and inconsistent ethephon conversion efficiency [46] [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators claimed that ethephon is not translocated at all [10,12,13] ; others demonstrated good and rapid translocation of 14 C-ethephon [21,23,24] . Still others reported that translocation occurs in some tissues but not in others [13,20], or that the moving compounds are actually labelled products of the 14 C-ethephon applied [9,13,14] . The present data support the view that translocation is limited or does not occur, but as the studies were conducted with old tissues (leaves 18 months old, fruit and pedicels 6 months old), the data fit also the conclusion of immobility in older tissues [13,20] .…”
Section: Discussionmentioning
confidence: 99%